2013
DOI: 10.1017/s1461145713000928
|View full text |Cite
|
Sign up to set email alerts
|

Translating the N-methyl-d-aspartate receptor antagonist model of schizophrenia to treatments for cognitive impairment in schizophrenia

Abstract: The N-methyl-D-aspartate receptor (NMDAR) antagonists, phencyclidine (PCP), dizocilpine (MK-801), or ketamine, given subchronically (sc) to rodents and primates, produce prolonged deficits in cognitive function, including novel object recognition (NOR), an analog of human declarative memory, one of the cognitive domains impaired in schizophrenia. Atypical antipsychotic drugs (AAPDs) have been reported to improve declarative memory in some patients with schizophrenia, as well as to ameliorate and prevent the NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 137 publications
(150 reference statements)
2
70
0
Order By: Relevance
“…Previous studies demonstrated the activation of 5‐HT3A receptor could increase dopamine release (Liu, Thielen, Rodd, & Mcbride, 2006), and the elevation of dopamine might contribute to the improvement of schizophrenic symptoms (Díaz‐Mataix et al., 2005). Furthermore, lines of evidence indicated the ability of 5‐HT3 receptors to modulate the release of acetylcholine and GABA (gama‐amino butyric acid) (Choi et al., 2007), which were thought to be involved in antipsychotics efficiency (Meltzer et al., 2013). Whether risperidone functions though upregulating 5‐HT3A receptor, thus inducing the release of the neurotransmission is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated the activation of 5‐HT3A receptor could increase dopamine release (Liu, Thielen, Rodd, & Mcbride, 2006), and the elevation of dopamine might contribute to the improvement of schizophrenic symptoms (Díaz‐Mataix et al., 2005). Furthermore, lines of evidence indicated the ability of 5‐HT3 receptors to modulate the release of acetylcholine and GABA (gama‐amino butyric acid) (Choi et al., 2007), which were thought to be involved in antipsychotics efficiency (Meltzer et al., 2013). Whether risperidone functions though upregulating 5‐HT3A receptor, thus inducing the release of the neurotransmission is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The hypofunction of glutamatergic receptors is the pathophysiology of schizophrenia of the glutamatergic hypothesis, and the N-methyl-d-aspartate receptor (NMDAR) antagonists, such as dizocilpine (MK-801), phencyclidine, and ketamine, produce schizophrenia-like behavior and cognitive deficits (Gaspar, Bustamante, Silva, & Aboitiz, 2009;Lobellova et al, 2013;Meltzer et al, 2013). Acute treatment with MK-801 is extensively utilized to establish animal model of cognitive impairment, such as spatial learning and memory.…”
Section: Introductionmentioning
confidence: 99%
“…Aripiprazole is an atypical antipsychotic with a novel pharmacological profile that acts as a partial agonist of dopamine D 2 and D 3 and serotonin (5-HT) 5-HT 1A receptors, and as an antagonist for 5-HT 2A receptors (17,18). Aripiprazole has moderate affinity for histamine, α-adrenergic, and D 4 receptors, as well as the serotonin transporter; however, it has no appreciable affinity for cholinergic muscarinic receptors (17,18) Different NMDA receptor antagonist-induced experimental models have been investigated to demonstrate the cognitive impairments, and selective ligands for serotonin and adrenoceptors have been examined in these models (22,23). In addition, post-training administration of the specific 5-HT7 receptor antagonists, SB-269970 and DR-4004, improved MK-801-induced memory impairments in rat auto-shaping tasks (22).…”
Section: Discussionmentioning
confidence: 99%
“…Aripiprazole has moderate affinity for histamine, α-adrenergic, and D 4 receptors, as well as the serotonin transporter; however, it has no appreciable affinity for cholinergic muscarinic receptors (17,18) Different NMDA receptor antagonist-induced experimental models have been investigated to demonstrate the cognitive impairments, and selective ligands for serotonin and adrenoceptors have been examined in these models (22,23). In addition, post-training administration of the specific 5-HT7 receptor antagonists, SB-269970 and DR-4004, improved MK-801-induced memory impairments in rat auto-shaping tasks (22). Quetiapine reversed MK-801-induced deficits in the current study and this may be linked via the interactions between serotonin receptors and adrenoceptors.…”
Section: Discussionmentioning
confidence: 99%